Immune-Mediated Diseases from the Point of View of Psychoneuroimmunoendocrinology - Miguel A. Ortega; Cielo García-Montero; Oscar Fraile-Martinez; Miguel Angel Alvarez-Mon; Ana Maria Gómez-Lahoz; Guillermo Lahera; Jorge Monserrat; Roberto Rodriguez-Jimenez; Javier Quintero; Melchor Álvarez-Mon (Biology, 2022)
Immune-mediated inflammatory diseases (IMIDs) represent a large group of diseases (Crohn’s, ulcerative colitis, psoriasis, lupus, and rheumatoid arthritis) evidenced by systemic inflammation and multiorgan involvement. IMIDs result in a reduced quality of life and an economic burden for individuals, health care systems, and countries. In this brief descriptive review, we will focus on some of the common biological pathways of these diseases from the point of view of psychoneuroimmunoendocrinology (PNIE). PNIE consists of four medical disciplines (psychology, nervous system, immune system, and endocrine system), which are key drivers behind the health–disease concept that a human being functions as a unit. We examine these drivers and emphasize the need for integrative treatments that addresses the disease from a psychosomatic point of view.